2002
DOI: 10.1046/j.1468-8123.2002.00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of hydrocarbons from natural seeps to the water column and atmosphere

Abstract: Results from surface geochemical prospecting, seismic exploration and satellite remote sensing have documented oil and gas seeps in marine basins around the world. Seeps are a dynamic component of the carbon cycle and can be important indicators for economically significant hydrocarbon deposits. The northern Gulf of Mexico contains hundreds of active seeps that can be studied experimentally with the use of submarines and Remotely Operated Vehicles (ROV). Hydrocarbon flux through surface sediments profoundly al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
154
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(158 citation statements)
references
References 27 publications
1
154
1
2
Order By: Relevance
“…The Gulf of Mexico is a leaky oil field (Macdonald et al, 1994(Macdonald et al, , 2002(Macdonald et al, , 2004MacDonald et al, 2002MacDonald et al, , 2004Milkov and Sassen, 2000, 2003Sassen et al, , 2003Sassen and MacDonald, 1994). Natural oil seeps leave slicks on the sea surface that can be seen from space.…”
Section: Structural-type Sedimentary Hydrate Depositsmentioning
confidence: 99%
“…The Gulf of Mexico is a leaky oil field (Macdonald et al, 1994(Macdonald et al, , 2002(Macdonald et al, , 2004MacDonald et al, 2002MacDonald et al, , 2004Milkov and Sassen, 2000, 2003Sassen et al, , 2003Sassen and MacDonald, 1994). Natural oil seeps leave slicks on the sea surface that can be seen from space.…”
Section: Structural-type Sedimentary Hydrate Depositsmentioning
confidence: 99%
“…Recent studies have shown that methane transfer from marine and lacustrine seeps to the atmosphere is only effective when methane is transported by bubbles released in relatively shallow water (< 100 m water depth) (Leifer and Patro, 2002;MacDonald et al, 2002;Schmale et al, 2005;McGinnis et al, 2006). In most cases, even if a bubble reaches the surface with a significant size, most of the methane is dissolved into the water column and replaced by other stripped gases, particularly oxygen (in oxic conditions) and nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Gas bubbling into the water column induces a distinctive signature on singlebeam or side scan systems (Hornafius et al, 1999;Hovland and Judd, 1988;MacDonald et al, 2002). On high-resolution seismic records, regions of anomalous gas concentrations in the sub-surface may be associated with anomalous seismic character (originally proposed by Løseth et al, 2003;Heggland, 1998;Hovland et al, 1999;and Schüler, 1952; note that anomalous seismic character may also be caused by variations in attenuation and resonance).…”
Section: Shallow Gas and Indirect Evidences Off The Grand Rhône Rivermentioning
confidence: 99%